Azithromycin reduces airway inflammation induced by human rhinovirus in lung allograft recipients. Issue 12 (15th April 2019) - Ling, Kak‐Ming; Hillas, Jessica; Lavender, Melanie A.; Wrobel, Jeremy P.; Musk, Michael; Stick, Stephen M.; Kicic, Anthony
ABSTRACT: Background and objective: Human rhinovirus (RV) is a common upper and lower respiratory pathogen in lung allograft recipients causing respiratory tract exacerbation and contributing towards allograft dysfunction and long‐term lung decline. In this study, we tested the hypothesis that RV could infect both the small and large airways, resulting in significant inflammation. Methods: Matched large and small airway epithelial cells (AEC) were obtained from five lung allograft recipients. Primary cultures were established, and monolayers were infected with RV1b over time with varying viral titre. Cell viability, receptor expression, viral copy number, apoptotic induction and inflammatory cytokine production were also assessed at each region. Finally, the effect of azithromycin on viral replication, induction of apoptosis and inflammation was investigated. Results: RV infection caused significant cytotoxicity in both large AEC (LAEC) and small AEC (SAEC), and induced a similar apoptotic response in both regions. There was a significant increase in receptor expression in the LAEC only post viral infection. Viral replication was elevated in both LAEC and SAEC, but was not significantly different. Prophylactic treatment of azithromycin reduced viral replication and dampened the production of inflammatory cytokines post‐infection. Conclusion: Our data illustrate that RV infection is capable of infecting upper and lower AEC, driving cell death and inflammation. Prophylactic treatment with azithromycin was found to mitigate some of the detrimental responses. Findings provide further support for the prophylactic prescription of azithromycin to minimize the impact of RV infection. Abstract : We highlight the ability of human rhinovirus (RV) to infect both large and small airway epithelial cells of lung allograft recipients resulting in cell death and inflammation. Importantly, we show that prophylactic treatment with azithromycin predominantly mitigates viral replication and the resulting inflammatory effects of viral infection. See related Editorial